Ranking European capitals by exposure to heat waves and cold waves - Smid, Marek (2019)
Smid, M., Russo, S., Costa, A. C., Granell, C., & Pebesma, E. (2019). Ranking European capitals by exposure to heat waves and cold waves. Urban Climate, 27(March), 388-402. DOI: 10.1016/j.uclim.2018.12.010